2003
DOI: 10.1183/09031936.03.00118302
|View full text |Cite
|
Sign up to set email alerts
|

Is preparation for bronchoscopy optimal?

Abstract: The results of a questionnaire survey, of the current preparation for and practice of diagnostic bronchoscopy in England and Wales, are reported in this paper. The British Thoracic Society (BTS) has recently published guidelines on bronchoscopy and these provide a consensus statement on the current evidence base. There is no specific guidance on drugs or techniques, although it is recommended that all patients should be offered sedation, except where there are contraindications.In the present survey, there was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 15 publications
3
59
0
2
Order By: Relevance
“…Although there is a debate concerning the need for sedation in FOB [28,29], we always performed non-sedated bronchoscopy with very few exceptions. Rather old studies suggested that sedation was implicated as the cause of major averse events resulting from FOB [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a debate concerning the need for sedation in FOB [28,29], we always performed non-sedated bronchoscopy with very few exceptions. Rather old studies suggested that sedation was implicated as the cause of major averse events resulting from FOB [3,30].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of sedation is to facilitate patient comfort and satisfaction and to alleviate patient anxiety, cough and dyspnoea while reducing complications of the procedure [2][3][4]. According to a survey of registered members of the British Thoracic Society, .95% of centres routinely perform sedated bronchoscopy [5]. Optimal sedation for flexible bronchoscopy has been assessed in a number of studies evaluating different sedative drug regimens using single agents or combinations thereof [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of sedation is to achieve good patient tolerance, comfort and cooperation whilst reducing complications of the procedure [2][3][4]. A recent European survey has shown that .95% of centres routinely perform sedated bronchoscopy [5].…”
mentioning
confidence: 99%